Heme Biosynthetic Gene Expression Analysis With dPCR in Erythropoietic Protoporphyria Patients - Granata, Francesca; Brancaleoni, Valentina; Barman-Aksözen, Jasmin; Scopetti, Margherita; De Luca, Giacomo; Fustinoni, Silvia; Motta, Irene; Di Pierro, Elena; Graziadei, Giovanna (Frontiers in Physiology, 2022)
Background: The heme biosynthesis (HB) involves eight subsequent enzymatic steps. Erythropoietic protoporphyria (EPP) is caused by loss-of-function mutations in the ferrochelatase (FECH) gene, which in the last HB step inserts ferrous iron into protoporphyrin IX (PPIX) to form heme. Aim and method: The aim of this work was to for the first time analyze the mRNA expression of all HB genes in peripheral blood samples of patients with EPP having the same genotype FECH c.[215dupT]; [315-48T > C] as compared to healthy controls by highly sensitive and specific digital PCR assays (dPCR). Results: We confirmed a decreased FECH mRNA expression in patients with EPP. Further, we found increased ALAS2 and decreased ALAS1, CPOX, PPOX and HMBS mRNA expression in patients with EPP compared to healthy controls. ALAS2 correlated with FECH mRNA expression (EPP: r = 0.63, p = 0.03 and controls: r = 0.68, p = 0.02) and blood parameters like PPIX (EPP: r = 0.58 p = 0.06). Conclusion: Our method is the first that accurately quantifies HB mRNA from blood samples with potential applications in the monitoring of treatment effects of mRNA modifying therapies in vivo, or investigation of the HB pathway and its regulation. However, our findings should be studied in separated blood cell fractions and on the enzymatic level.